Liposomal Cytarabine as Cancer Therapy: From Chemistry to Medicine - Salehi, Bahare (Biomolecules, 2019)
Cancer is the second leading cause of death worldwide. The main modality to fight against cancer is surgery, radiotherapy, and chemotherapy, and more recently targeted therapy, gene therapy and immunotherapy, which play important roles in treating cancer patients. In the last decades, chemotherapy has been well developed. Nonetheless, administration of the drug is not always successful, as limited drug dosage can reach the tumor cells.. In this context, the possibility to use an encapsulated anti-cancer drug may potentially solve the problem. Liposomal cytarabine is a formulation with pronounced effectiveness in lymphomatous meningitis and reduced cardiotoxicity if compared to liposomal anthracyclines. Thus, the future liposomal cytarabine use could be extended to other diseases given its reduction in cytotoxic side effects compared to the free formulation. This review summarizes the chemistry and biology of liposomal cytarabine, with exploration of its clinical implications.